2018
DOI: 10.1002/lno.10775
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying nitrate dynamics in a mesotrophic lake using triple oxygen isotopes as tracers

Abstract: Vertical distributions of both concentrations and stable isotopic compositions of nitrate, including the 17 O-excesses (D 17 O), were determined four times during 1 yr within the mesotrophic water column of Lake Biwa in Japan. By using both the deposition rate of atmospheric nitrate onto the entire surface of the lake and the influx/efflux of both atmospheric and remineralized nitrate via streams reported in the literature, we quantified the annual dynamics of nitrate (gross production rate of nitrate through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
2
19
0
Order By: Relevance
“…The δ 2 H values determined in this study (−222 ± 57‰ for the littoral zone and −277 ± 6‰ for the pelagic sediments) were enriched in deuterium, compared to methane in typical freshwater environments, such as wetlands and rice paddies (Whiticar et al 1986; Sugimoto and Wada 1993; Nakagawa et al, 2002 a , b ; Chanton et al 2005). Based on the empirical relation between δ 2 H of water and δ 2 H of methane, which was obtained experimentally through incubating freshwater soil (Sugimoto and Wada 1993), we can estimate the δ 2 H value of methane produced via CO 2 reduction as −355 ± 20‰ and the δ 2 H value via acetate fermentation as −326 ± 15‰, with water (H 2 O) having a δ 2 H value of −55‰ (the δ 2 H value of lake water; Tsunogai et al 2018). Still, we concluded that methane production in anoxic sediments via the CO 2 reduction pathway was a reasonable source for these values, as explained below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The δ 2 H values determined in this study (−222 ± 57‰ for the littoral zone and −277 ± 6‰ for the pelagic sediments) were enriched in deuterium, compared to methane in typical freshwater environments, such as wetlands and rice paddies (Whiticar et al 1986; Sugimoto and Wada 1993; Nakagawa et al, 2002 a , b ; Chanton et al 2005). Based on the empirical relation between δ 2 H of water and δ 2 H of methane, which was obtained experimentally through incubating freshwater soil (Sugimoto and Wada 1993), we can estimate the δ 2 H value of methane produced via CO 2 reduction as −355 ± 20‰ and the δ 2 H value via acetate fermentation as −326 ± 15‰, with water (H 2 O) having a δ 2 H value of −55‰ (the δ 2 H value of lake water; Tsunogai et al 2018). Still, we concluded that methane production in anoxic sediments via the CO 2 reduction pathway was a reasonable source for these values, as explained below.…”
Section: Resultsmentioning
confidence: 99%
“…17B and 12B, respectively, managed by the Lake Biwa Environmental Research Institute. The details of the field campaigns have already been reported, together with concentration and stable isotopic compositions of nutrients in the lake water samples collected simultaneously in 2013 (Tsunogai et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The concentrations of NO 3 -were measured by ion chromatography (DX-500, Dionex Inc., USA), together with major anions and cations. Samples were analyzed within a few weeks of sampling then sealed in 50 or 100 mL polyethylene bottles for further analysis, including measurement of the isotopes in the stream and 25 (Konno et al, 2010;Tsunogai et al, 2008;Tsunogai et al, 2018;Yamazaki et al, 2011). In brief, the procedure was as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dual isotope measurements of both NO 2 and NO 3 have revealed NO 3 regeneration in the euphotic zone and in O 2 deficient zones (e.g., Sigman et al ), and thus nitrification is now recognized to play a significant role in the oceanic N cycle (e.g., Casciotti and Buchwald ). Recently, triple isotopes (δ 15 N, δ 18 O, and Δ 17 O of NO 3 ) have been applied to the study of rates of nitrification and the assimilation of NO 3 in streams (Rose et al ) and lakes (Tsunogai et al ). Due to the fact that atmospheric NO 3 generally has positive Δ 17 O values, while microbially derived NO 3 has Δ 17 O values ≤ 0, measurements of Δ 17 O of NO 3 were found to reliably resolve atmospheric NO 3 − and collectively, the isotope analyses yielded gross nitrification and metabolic rates of NO 3 − where there were detectable quantities of NO 3 in the water column.…”
Section: A Deeper Dive: Insights From Classic To Cutting‐edge Isotopementioning
confidence: 99%